Training on the Preparation of Problem Based Learning and Project Based Learning Materials for Chemistry Teachers in the 5th Region of West Sumatera - Zonalia Fitriza; Yerimadesi Yerimadesi; Faizah Qurrata Aini; Mawardi Mawardi; Lillah Fitri; Nadia Julianti; Ifan Rivaldo (Fakultas MIPA Universitas Negeri Padang, 2022)
Chemistry Teacher Association of the 5th region in West Sumatera is a discussion media for chemistry teacher in Sijunjung, Sawahlunto, and Darmasraya District. There are 33 Senior High School in these area with 42 members. They have difficulty in implementing Problem Based Learning and Project Based Learning model due to lack of understanding. Some expected competences in the 2013 curriculum require teaching learning process to be conducted by PBL dan PjBL particularly the competences with operational verb “designing and creating”. Moreover, they do not have any teaching material based on PBL and PjBL since these kinds of learning models have to provide contextual problems related to chemisty topics. Students will propose solutions and products, via discussion and project. The training successed in guiding teachers to compile 8 PBL and 6 PjBL learning materials.